Protocol? or deferential and deep solidarity towards ill patients? - María Teresa Miralles Sangro (Universidad de Alicante, 2012)
Portraits of sick people showing their illnesses were not really frequent along XIX century, compared to the full production of Spanish painters. This premise together with my own surprise at the discovering of the piece of art I herewith consider, were determinant on my decision to develop the present study. The piece of art, is a portrait by José Roldán painted around 1864, Her Majesty Queen Elizabeth II in the act of kissing the hand of the poorest and eldest man in the Charity Hospital of Seville. The reason for this study goes around the description of attitudes and behaviour towards the ill patient and his/her care taker in the Elizabethan Spanish period. It is a descriptive and interpreting study where characters appearing on the stage would be considered according to the events they are suppose to take part in. Who they are, why they are where they are and what sort of role they do perform. The piece of work was exhibited by Roldán in the National Exhibition 1864. It could be regarded within a Seville genre presenting a society of extreme Christian habits and their interest in religious processions, charity and festivity and civil celebrations. In the analyzed portrait nothing is merely accidental, those characters present must be present. Nursing, still voiceless at that time justifies punctually and clearly its presence there as there is an ill person who needs 'care'. The argument is the satisfaction of his vital needs be fulfilled.